Mesenchymal stem cells in rheumatoid synovium: enumeration and functional assessment in relation to synovial inflammation level. Issue 2 (2nd April 2009) - Jones, E; Churchman, S M; English, A; Buch, M H; Horner, E A; Burgoyne, C H; Reece, R; Kinsey, S; Emery, P; McGonagle, D; Ponchel, F
Abstract : Objective: Achieving joint regeneration in rheumatoid arthritis (RA) represents a future challenge. Autologous synovial mesenchymal stem cells (MSCs) could be therapeutically exploited. However, the inflammatory milieu in the RA synovium could adversely affect endogenous MSC function. To test this hypothesis, the frequency and multipotency of RA synovial MSCs was evaluated in relation to existing synovial inflammation. Methods: Synovial inflammation was measured using the arthroscopic visual analogue score (VAS) and further validated using immunohistochemistry and flow cytometry. Highly proliferative clonogenic in vivo MSCs were enumerated following fluorescence-activated cell sorting and expansion for 20 population doublings. MSC multipotency was quantified following standard in vitro culture expansion and trilineage differentiation assays. Real-time PCR, flow cytometry and ELISA were used to evaluate pro- and anti-chondrogenic molecules in standard polyclonal synovial MSCs. Results: The arthroscopic VAS significantly correlated with synovial macrophage infiltration. In RA, synovial MSC chondrogenesis was inhibited in direct relation to VAS (r = −0.777, p<0.05) and reduced compared with control osteoarthritis (OA)-MSCs (p<0.05). In vivo, MSCs resided in the synovial fibroblastic/stromal fraction (CD45 − CD31 − ) and were reduced in frequency in relation to VAS (r = −0.695, p<0.05). In RA-MSCs, CD44 levels correlated negatively with inflammation and positively with chondrogenesis (r = −0.830 and r = 0.865, respectively). Cytokine production and Sox9 expression was similar in RA-MSCs and OA-MSCs. Conclusions: There is a negative relationship between synovial MSC chondrogenic and clonogenic capacities and the magnitude of synovitis in RA. Effective suppression of joint inflammation is therefore necessary for the development of autologous MSC treatments aimed at cartilage regeneration in RA.